The Complexity Turn : Cultural, Management, and Marketing Applications. - Woodside, Arch G. (Springer, 2017)
This book takes the reader beyond net effects and main and interaction effects thinking and methods. Complexity theory includes the tenet that recipes are more important than ingredients--any one antecedent (X) condition is insufficient for a consistent outcome (Y) (e.g., success or failure) even though the presence of certain antecedents may be necessary. A second tenet: modeling contrarian cases is useful because a high or low score for any given antecedent condition (X) associates with a high Y, low Y, and is irrelevant for high/low Y in some recipes in the same data set. Third tenet: equifinality happens--several recipes indicate high/low outcomes.
Keywords: Management.; elektronické knihy; electronic books